Inhibitory Effect of Dexamethasone on TGF-β1 Expression of Rabbit Ciliary Pigment Epithelia Cultured in Vitro - 熊新春 席祖莲 苗娟 李庆林 张海江 胡义珍 魏厚仁 (Journal of Huazhong University of Science and Technology. Medical sciences, 2006)
In order to elucidate the effect of dexamethasone on the expression of transforming growth factor-betal （TGF-β1） in ciliary pigment epithelial （CPE） cells cultured in vitro, rabbit CPE cells were cultured in vitro, treated with DMEM medium containing 0, 1 × 10^-8 , 5 × 10^-8 , 10 × 10^-8 and 50 × 10^-8 mol/L dexamethasone respectively for 5 days. The TGF-131 expression was detected by immunohistochemistry Supervision methods and analyzed semi-quantitatively by HMIAS-2000 image system. As opposed to in vivo, rabbit CPE cells expressed TGF-131 under cul- tured circumstance in vitro. The gray scales of the positive yellow staining in the groups of 1 × 10^-8 , 5 × 10^-8 , 10 × 10^-8 and 50 × 10^-8 mol/L dexamethasone were 136.57 ± 4.43, 140.20 ± 6. 10, 142. 98± 2. 99, 146.80±1.68 and 150.05 × 1.94 respectively. When the concentrations of dexamethasone were equal to or higher than 5 × 10^-8mol/L and, the expression of TGF-β1 was inhibited. 10^-7 mol/L dexamethasone showed a significant inhibition. It was suggested that CPE cells possess the potential ability of synthesizing and expressing TGF-β1. The inhibition of TGF-β1 expression by dexamethasone may be beneficial to the treatment of proliferative vitroretinopathy, also exert some influence on the secretion of aqueous humor and ciliary inflammation.